Faz um pix! Equilibrando controle e generatividade em sistema nacional de pagamentos - Nascimento, Gabriel Medeiros do (2023)
Generativity is an essential characteristic for digital platforms. It is the platform's ability to have its content guided and programmed by third parties who are not guided and spontaneously involved with the system. The opposite movement, of limitation of this creative activity, is called control. This research answered the question: how does the Central Bank, owner of Pix, control generativity in the famous national platform for Brazilian payments? Based on this question, the specific objectives were to identify ways in which the Central Bank guides generativity on the platform, as well as listing generative opportunities on Pix and how these relate to possible control strategies applied by the Central Bank on Pix. For this, an exploratory and qualitative research methodology was adopted. The primary sources were academic articles, technical documentation, rules and regulations. As secondary sources, we had reports and materials from communication vehicles and journalism. Based on analyzes of Pix's technical manuals regarding Security, Interfaces and domains as such, we sought to identify the balance strategy between control and generativity employed by the Central Bank in managing Pix. The use of a hybrid methodology was identified to balance control and generativity, in the "domain-structural" aspect. That is, the Central Bank modulates the quality of generativity depending on the domain of the platform and the type of third party involved, whether user or partner financial institution.